2013
DOI: 10.1097/coc.0b013e31823a4956
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lymphedema in Patients With Axillary Lymph Node Dissections to Those With Sentinel Lymph Node Biopsy Followed by Immediate and Delayed ALND

Abstract: The rate of lymphedema was higher in delayed ALND but not statistically significant. Comparison, however, is difficult, given the limited sample size. We urge the other centers of NSABP-B32 to validate this, by contacting the node-positive patients for measurements. The lymphedema rate for SLNB alone was 0% and approached statistical significance when compared with node-negative ALND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The data from the current study identified ALND and RNI as two factors associated with the development of subclinical BCRL. These observations are consistent with previous studies that also found these factors (along with taxane chemotherapy and an elevated BMI) to be associated with the development of BCRL [ 4 , 7 9 , 19 22 , 25 , 26 ]. Additionally, a recent study from Turkey which utilized BIS and circumference arm measurements found BMI, number of nodes involved, and capsular invasion to be associated with BCRL, with the number of positive nodes also correlating with the L-Dex score [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…The data from the current study identified ALND and RNI as two factors associated with the development of subclinical BCRL. These observations are consistent with previous studies that also found these factors (along with taxane chemotherapy and an elevated BMI) to be associated with the development of BCRL [ 4 , 7 9 , 19 22 , 25 , 26 ]. Additionally, a recent study from Turkey which utilized BIS and circumference arm measurements found BMI, number of nodes involved, and capsular invasion to be associated with BCRL, with the number of positive nodes also correlating with the L-Dex score [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…10 However, Kuwajerwala and colleagues found no statistically significant difference in the lymphoedema rate between immediate versus delayed ALND, although the rate of lymphoedema was higher in the delayed group (10.3% vs 14.3%, P > .05). 23 Ballal et al published our institution's results from 2008 to 2012, which also demonstrated no statistically significant difference in the lymphoedema rates between immediate versus delayed ALND (17.8% vs 8.6%). 19 In our current study, the results reflect our prior institution's results with no statistically significant difference in postoperative lymphoedema.…”
Section: Discussionmentioning
confidence: 62%
“…1,2 However, an SLNB is not only still invasive, it is also associated with several postoperative complications, such as lymphedema, sensory loss, and upper limb pain. 3,4 Furthermore, the incidence of SLN metastasis in clinical axillary LNnegative patients was reported to be 23.0-37.1%, [5][6][7][8] and approximately 70-80% of patients receive excessive invasive axillary surgery. If predictive factors of SLN metastasis could be identified, we might be able to select candidate patients for an SLNB.…”
Section: Introductionmentioning
confidence: 99%